Neutrino emission from gamma-ray bursts - Vieyro, Florencia Laura (2014)
Gamma-ray bursts (GRBs) are the most violent and energetic events in the universe. Short GRBs seem to be the result of the final merger of two compact objects, whereas long GRBs are probably associated with the gravitational collapse of very massive stars (collapsars). The central engine of a GRB can collimate relativistic jets, where shocks are produced and particles can be accelerated. Although the exact location of the region where the gamma rays are created is still under debate, it is widely accepted that the prompt emission has a different origin from the afterglow. The latter is emitted at a much greater distance from the central engine, when the fireball is decelerated by its interaction with the interstellar medium. It seems reasonable to assume that if the prompt gamma-ray radiation and the afterglows are generated by relativistic electrons accelerated in shocks, then the same shocks should also accelerate baryons. These high-energy protons can produce neutrinos through pp inelastic collisions and pγ interactions, making GRBs candidates to be sources of high-energy neutrinos. In this review, I discuss different scenarios where high-energy neutrinos (GeV-EeV) can be generated.